From the anal canal to the pancreas: diagnostic challenges of radiologic surveillance in detecting rare but potentially curable metastases — a case report - Stanić, Jelena; Šović, Ivana; Jovanović, Luka; Nikić, Predrag; Arsenijević, Tatjana (Frontiers in Oncology, 2026)
IntroductionPancreatic metastases from anal canal squamous cell carcinoma (SCC) are exceptionally rare. To date, only one previous case has been reported. The present case represents the second documented instance, highlighting the unusual metastatic pattern and the challenges in diagnosis and treatment. Due to the rarity of such metastases, their clinical presentation and optimal management remain poorly understood.Case presentationWe describe a 64-year-old woman diagnosed with locally advanced anal canal SCC, with diagnosis delayed as she had deferred medical consultation, who then received definitive chemoradiotherapy. During routine follow-up imaging, a small pancreatic lesion was initially overlooked and not reported. One and a half years later, the patient presented with nonspecific abdominal symptoms, and imaging revealed a 5 cm pancreatic mass. Endoscopic ultrasound-guided biopsy confirmed metastatic SCC of anal origin. The mass was considered inoperable due to vascular invasion. Systemic chemotherapy induced partial remission; however, due to hematologic toxicity, treatment was modified, and stereotactic body radiotherapy was applied to the pancreatic lesion, resulting in disease stabilization. Subsequent pulmonary metastases were treated with second-line chemotherapy, resulting in further partial remission; however, later disease progression was observed, limited to the pancreas, and third-line chemotherapy was planned but not initiated due to deterioration of general condition.ConclusionThis case highlights the importance of vigilant long-term surveillance and multidisciplinary management in patients with anal SCC, especially when atypical metastatic sites like the pancreas are involved. Early identification and histopathological confirmation enable timely, targeted treatment, which can improve clinical outcomes in such rare presentations.